1998
DOI: 10.1177/1045389x9800900708
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Active-Parametric Control Approach for Active-Passive Hybrid Piezoelectric Network with Variable Resistance

Abstract: Previous studies have shown that piezoelectric materials can be used to provide passive damping by shunting them with an electrical network, such as a series RL circuit. This same configuration can also be used in conjunction with an active voltage source as an active-passive hybrid vibration control method. This active-passive piezoelectric network (APPN) concept, which combines the advantages of passive damping and active control, has proven to be very effective for vibration suppression, especially in narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Therefore, as will be demonstrated in the following experiments, the vibration phase relations in Eqs. (9)(10)(11)(12) are still valid in the hybrid system. The next section describes various aspects of the three logics.…”
Section: Switching Logic For Hybrid Vibration Suppressionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, as will be demonstrated in the following experiments, the vibration phase relations in Eqs. (9)(10)(11)(12) are still valid in the hybrid system. The next section describes various aspects of the three logics.…”
Section: Switching Logic For Hybrid Vibration Suppressionmentioning
confidence: 95%
“…Morgan and Wang [12] indicated that direct implementation of a rate feedback control law may lead to instability in APPN systems, due to the effects of circuit dynamics. Our work may provide a systematic analysis of their finding, although their variable-resistance system was different from ours and they used the time-derivative of voltage of a piezosensor.…”
Section: Vibration Suppression Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-active vibration absorbers can be separated into several types: variable stiffness through mechanical mechanisms [2,8,16,17] or using controllable new materials [6,12,13,18], variable inductor connected in series with the piezoelectric patch for piezoelectric absorbers [7,[9][10][11]. The first two types are used widely which can be tuned to the varying frequency by changing their resonant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, semi-active and active-passive vibration absorbers have been proposed to suppress harmonic excitations with time-varying frequency [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Semi-active vibration absorbers can be separated into several types: variable stiffness through mechanical mechanisms [2,8,16,17] or using controllable new materials [6,12,13,18], variable inductor connected in series with the piezoelectric patch for piezoelectric absorbers [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%